First step is to write one equation as one variable in terms of another variable.
From the given, we have two equations :
Equation 1 :
3x + 5y = 2
Equation 2 :
x + 3y = 4
Rewrite Equation 2 as the step above.
![\begin{gathered} x+3y=4 \\ x=4-3y \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y7gf68s6w5i8x2tdnzbo3nw9v4yb8v3wzp.png)
2nd step is to substitute the resulting equation to Equation 1 :
![\begin{gathered} 3x+5y=2 \\ 3(4-3y)+5y=2 \\ 12-9y+5y=2 \\ -4y=2-12 \\ -4y=-10 \\ y=(-10)/(-4)=(5)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ffq15ebhe63v2yyjhc9cu4h5ginngu9uav.png)
3rd step is to substitute this y value to Equation 2 :
![\begin{gathered} x=4-3y \\ x=4-3((5)/(2)) \\ x=4-(15)/(2) \\ x=-(7)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7xh62cxeuqk5sp13aprlwb5x33jjmaai1m.png)
The intersection is at (x, y)
The answer is (-7/2, 5/2)